2019
DOI: 10.1242/jeb.206680
|View full text |Cite
|
Sign up to set email alerts
|

CB1 and CB2 receptors play differential roles in early zebrafish locomotor development

Abstract: Endocannabinoids (eCBs) mediate their effects through actions on several receptors, including the cannabinoid receptors CB 1 R and CB 2 R. The role played by eCBs in the development of locomotor systems is not fully understood. In this study, we investigated the roles of the eCB system in zebrafish development by pharmacologically inhibiting CB 1 R and CB 2 R (with AM251 and AM630, respectively) in either the first or second day of development. We examined the morphology of motor neurons and we determined neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Using HEK cells several receptor candidates have been identified showing to interact with CBD 25 . A recent study supports a functional role of CB1R and CB2R in zebrafish 32 . Here, by inhibiting CB1R, and CB2R, we found that the reduction in locomotor activity mediated by CBD was partially prevented at nanomolar concentrations of the inhibitors.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Using HEK cells several receptor candidates have been identified showing to interact with CBD 25 . A recent study supports a functional role of CB1R and CB2R in zebrafish 32 . Here, by inhibiting CB1R, and CB2R, we found that the reduction in locomotor activity mediated by CBD was partially prevented at nanomolar concentrations of the inhibitors.…”
Section: Discussionsupporting
confidence: 58%
“…Translucent larvae provide opportunities to implement cutting-edge fluorescing calcium sensors and measure neural activity. Past studies suggest that the endocannabinoid system plays a role in zebrafish development 3032 . In addition, both cannabinoid receptors investigated here have similar expression profiles in the CNS compared to mammals, with CB1R sharing a 70 % protein sequence identity with the human homolog 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Translucent larvae provide opportunities to implement cutting-edge fluorescing calcium sensors and to measure neural activity. The endocannabinoid system plays a role in zebrafish development 30 32 . CB1R and CB2R have similar expression profiles in the CNS of zebrafish compared to mammals, and CB1R shares a 70% protein sequence identity with its human homolog 33 .…”
Section: Introductionmentioning
confidence: 99%
“…While both CB1R and CB2R transcripts were identified in the human trophoblast during the first trimester, in vitro experiments demonstrated that anandamide prevented the proliferation of BeWo trophoblast cells via the CB2R [ 227 ]. In a recent study using zebrafish embryos, it was demonstrated that blocking CB2Rs during early development resulted in a greater inhibition of heart rate than that observed with a CB1R blocker [ 228 ]. Additionally, both CB1Rs and CB2Rs were also reported in embryonic stem cells (ESC) [ 229 , 230 ].…”
Section: Biological Role Of the Cannabinoid Receptorsmentioning
confidence: 99%